2010
DOI: 10.1186/1472-6963-10-53
|View full text |Cite
|
Sign up to set email alerts
|

Doctor as criminal: reporting of patient deaths to the police and criminal prosecution of healthcare providers in Japan

Abstract: BackgroundIn Japan, medical error leading to patient death is often handled through the criminal rather than civil justice system. However, the number of cases handled through the criminal system and how this has changed in recent years has not previously been described. Our aim was to determine the trend in reports of patient death to the police and the trend in the resulting prosecution of healthcare providers for medical error leading to patient death from 1998 to 2008.MethodsWe collected data regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Consequently, these topics have been incorporated into the curricula of more than three quarters of schools. The Hiroo case was a sentinel case handled through the Japanese criminal legal system, and subsequent cases of medical error have been handled likewise; prior research has shown the total number of healthcare provider criminal prosecutions for medical error leading to patient death has been on the rise for over 10 years [ 31 ]. This may be why so many nursing schools cover the topics of criminal liability.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these topics have been incorporated into the curricula of more than three quarters of schools. The Hiroo case was a sentinel case handled through the Japanese criminal legal system, and subsequent cases of medical error have been handled likewise; prior research has shown the total number of healthcare provider criminal prosecutions for medical error leading to patient death has been on the rise for over 10 years [ 31 ]. This may be why so many nursing schools cover the topics of criminal liability.…”
Section: Discussionmentioning
confidence: 99%
“…This measure has been translated into Spanish [111]. Self-rated/self-reported health (SRH) has been differentially reported by Hispanics compared to whites, especially based on their acculturation status [111-114]. Hispanics are 3.6 times more likely to report fair or poor health compared to whites [115].…”
Section: Methodsmentioning
confidence: 99%
“…In 1999, two serious medical accidents occurred at about the same time that the Institute of Medicine (IOM) report "To Err is Human" was published in the United States. One medical accident occurred at Yokoham City University Hospital (YUCH) [35] in January of 1999 while the other occurred at Hiroo General Hospital (HGH) in February of 1999 [36]. At YUCH two patients were mixed-up: a patient who needed a heart operation was mistaken for another patient who required a lung operation.…”
Section: Initiatives In Japan Focusing On Patient Safety and The Elecmentioning
confidence: 99%